Access for All : Building Inclusive Financial Systems - Helms, Brigit (Washington, DC: World Bank, 2012)
The Consultative Group to Assist the Poor (CGAP), a multi-donor consortium dedicated to advancing microfinance, is a global resource center for microfinance standards, to provide operational tools, training, and advisory services, committed to building more inclusive financial systems for the poor. Meeting the challenge of placing resources and power into the hands of poor and low-income people themselves, is the topic of this book. It is also the main focus of the CGAP, a vision about inclusive financial systems, the only way to reach large numbers of poor and low-income people. To get there, diverse approaches are needed, reviewed through a look at microfinance, its history, process and progress. The book offers a compendium of CGAP's learning and experience over the past decade, opening a new chapter in its ongoing work: to dramatically expand access to financial services.